Organisasi Remaja Masjid Sebagai Kontrol Sosial Remaja Kelurahan Tanjung Uncang Kota Batam - Muhamad Andreansyah; Nanik Rahmawati; Rahma Syafitri (LPPM Universitas Sains dan Teknologi Komputer, 2024)
Juvenile delinquency in society, apart from awareness among teenagers, there is also a need for assistance from external parties such as parents, community leaders and organizations or institutions to help control teenagers. Mosque youth is one of the external youth institutions which can be a means of social control for teenagers in society, which as the name suggests is a religious organization, by instilling spiritual and physical values, it is hoped that mosque youth organizations can become a means of control for teenagers in their environment. Data collection techniques use direct observation and structured interviews to obtain data. The theory used in this research is F.Ivan Nye's social control. F.Ivan Nye's social control theory explains his various assumptions regarding the importance of controlling teenagers so that they do not commit deviations and what is needed to establish control. The research results show that mosque youth organizations as a tool of social control fulfill F.Ivan Nye's assumptions regarding various aspects needed to carry out control such as instilling values and providing good socialization to teenagers so that they then become aware of themselves to comply with existing laws and values.